2016
DOI: 10.1111/ahg.12160
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNAs and Life Expectancy Among Identical Twins

Abstract: Summary Human life expectancy is influenced not only by longevity assurance mechanisms and disease susceptibility loci but also by the environment, gene-environment interactions, and chance. MicroRNAs (miRNAs) are a class of small noncoding RNAs closely related to genes. Circulating microRNAs have been shown as promising non-invasive biomarkers in the development of many pathophysiological conditions. However, the concentration of miRNA in the circulation may also be affected by environmental factors. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Many miRNAs have been previously demonstrated to be differentially expressed in cells, tissues, whole blood [ 10 , 73 , 74 , 75 ], plasma [ 76 , 77 , 78 ], and serum [ 79 , 80 , 81 ] in relation to age.…”
Section: Micrornas As Aging Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…Many miRNAs have been previously demonstrated to be differentially expressed in cells, tissues, whole blood [ 10 , 73 , 74 , 75 ], plasma [ 76 , 77 , 78 ], and serum [ 79 , 80 , 81 ] in relation to age.…”
Section: Micrornas As Aging Biomarkersmentioning
confidence: 99%
“…The analysis of plasma circulating miRNA from a twin study conducted by the National Heart, Lung, and Blood Institute identified significantly up-regulated miR-3615 and miR-619 in younger deceased twins compared to their longer-lived co-twin. Additionally, the increased expression of miR-423-5p and miR-4305 was detected in less than 70% of short-lived twins [ 76 ]. In this study, changes in the remaining longevity-related miRNAs were not significant, potentially due to a small sample size.…”
Section: Micrornas As Aging Biomarkersmentioning
confidence: 99%
“…Moreover, we had to incorporate CHD of different morphological and clinical types and severity, due to the low incidence of monozygotic twins discordant for CHD. Since it has been shown that even non-CHD monozygotic twins display a considerable variation of their miRNA fingerprints [29], we were prepared to encounter a highly complex and heterogeneous picture. It is a challenge to recruit and assay monozygotic twins and even collect data for a given phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been investigated as biomarkers for MZ twins’ identification because several studies reported some disease-related miRNAs as differentially expressed in MZ twins [ 114 , 115 , 116 ].…”
Section: Mirnas and Discrimination Of Monozygotic Twinsmentioning
confidence: 99%